2001
DOI: 10.1002/neu.1036
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of survival and growth in adult sympathetic neurons: An invitro study of neurotrophin responsiveness

Abstract: The survival and growth of embryonic and postnatal sympathetic neurons is dependent on both NGF and NT3. While it has been established that adult sensory neurons survive independently of neurotrophins, the case is less clear for adult sympathetic neurons, where the studies of survival responses to neurotrophins have relied upon using long-term cultures of embryonic neurons. We have previously established a method to culture purified young (7 day) and adult (12 week) sympathetic neurons isolated from adult rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…It has also been previously suggested that physiological overexpression of certain receptor types may lead to dimerization of receptor monomers resulting in phosphorylation and basal activation (Penuel et al, 2002). This type of crosstalk has been suggested to contribute to the ability of mature neurons to survive in the absence of neurotrophin (Orike et al, 2001). (2) Low levels of autophosphorylation may also be caused by a physiological level of basal activation, as it has been shown for G protein-coupled receptors (Teitler et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…It has also been previously suggested that physiological overexpression of certain receptor types may lead to dimerization of receptor monomers resulting in phosphorylation and basal activation (Penuel et al, 2002). This type of crosstalk has been suggested to contribute to the ability of mature neurons to survive in the absence of neurotrophin (Orike et al, 2001). (2) Low levels of autophosphorylation may also be caused by a physiological level of basal activation, as it has been shown for G protein-coupled receptors (Teitler et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…The cells were then cultured in neurobasal/B27 medium following the method used in our previous study (Li et al, 2000). For culturing sympathetic neurons, superior cervical ganglia were dissected from 3-to 4-week-old rats using the method as described previously (Orike et al, 2001) with some modifications. The ganglia were desheathed, minced into 8 -10 pieces, and treated enzymatically in 1ϫ HBSS buffer containing 1.0 mg/ml collagenase, 0.0625 mg/ml trypsin, and 0.0625 mg/ml DNase at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether HAP1 is also present in TrkA-containing primary neurons, we used anti-HAP1 to stain cultured sympathetic neurons isolated from adult rat superior cervical ganglia, a cell model that has been widely used to study TrkA (Orike et al, 2001;Kuruvilla et al, 2004). Both HAP1 and TrkA are specifically enriched in sympathetic neurons and their neurites (Fig.…”
Section: Hap1 Stabilizes Intracellular Trkamentioning
confidence: 99%
“…Similarly, sympathetic and sensory neurons exhibit reduced responsiveness to a mutated NGF protein with reduced binding to p75 but wildtype binding to trkA (Horton et al ., 1997). Activated p75 and trkA mediate positive growth responses to NGF in adult sympathetic neurons (Orike et al , 2001b) and are required for NGF uptake and retrograde transport in adult sympathetic neurons (Gatzinsky et al ., 2001), despite the possibility that p75, when activated alone, exerts negative effects on growth (Kohn et al ., 1999). In sympathetic neurons, NT3 appears also to act through trkA and through p75 rather than through its cognate receptor, trkC Dechant et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%